Patient gender and rotator cuff surgery: are there differences in outcome? - Marlis T. Sabo; Justin LeBlanc; Kevin A. Hildebrand (BMC Musculoskeletal Disorders, 2021)
Abstract Background Although rotator cuff syndrome is common and extensively studied from the perspective of producing healed tendons, influence of gender on patient-reported outcomes is less well examined. As activity and role demands may vary widely between men and women, clarity on whether gender is an important factor in outcome would enhance patient education and expectation management. Our purpose was to determine if differences exist in patient-reported outcomes between men and women undergoing rotator cuff surgery. Methods One hundred forty-eight participants (76 W:72 M) aged 35–75 undergoing surgery for unilateral symptomatic rotator cuff syndrome were followed for 12 months after surgery. Demographics, surgical data, and the Western Ontario Rotator Cuff (WORC) scores were collected. Surgery was performed by two fellowship-trained shoulder surgeons at a single site. Results There were no gender-based differences in overall WORC score or subcategory scores by 12 months post-op. Pain scores were similar at all time points in men and women. Women were more likely to have dominant-arm surgery and had smaller rotator cuff tears than men. Complication rates were low, and satisfaction was high in both groups. Conclusion Patient gender doesn’t appear to exert an important effect on patient-reported rotator cuff outcomes in this prospective cohort. Further work examining other covariates as well as the qualitative experience of going through rotator cuff repair should provide greater insight into factors that influence patient-reported outcomes.